Assessment of pain and swelling following surgical extraction of impacted mandibular third molar using complete and partial wound closure techniques in a tertiary institution - Thomas Owobu; Babatunde O. Bamgbose; Abubakar M. Kaura; Ibisola O. Amole; Junichi Asaumi (Journal of Dentomaxillofacial Science, 2019)
Objective: Surgical extraction of impacted mandibular third molars is complicated by pain and swelling. The surgical wound can be closed either partially or completely. This study compared the incidence of postoperative pain and swelling between partial and complete wound closure techniques.Material and Methods: 120 consenting subjects were randomly allocated into two groups. Group 1 had complete wound closure while Group 2 had partial closure.  The mean duration of surgery was 3.63 minutes higher in complete wound closure than the partial wound closure technique.  The research subjects were evaluated for the degree of pain and swelling at 24 hours, 3rd and 5th days postoperatively using verbal rating scale (VRS) for pain and visual analogue scale (VAS)for swelling. The chi (x2) test was used to determine associations between categorical variables, and a p-value of 0.05 or less was considered significant in this study. Repeated measures ANOVA was done for pain and swelling.Results: There were 62 (51.7%) males and 58 (48.3%) females; age range was 18 to 45 years and mean age was 31.7±5.7. Pain and swelling was maximal on the first postoperative day and this gradually reduced over time. Post hoc tests using Bonferroni correction revealed that wound closure technique elicited a reduction in pain from Day 1, Day 3 to Day 5 (2.92±0.28, 1.18±0.65 and 0.34±0.48, respectively) which was statistically significant (p=0.000). There was a significant difference in swelling between the two techniques (p=0.000).Conclusion: The wound closure technique elicits a statistically significant reduction in postoperative pain and swelling. The partial third molar wound closure technique provides greater reduction in postoperative pain and swelling.